Music expertise shapes audiovisual temporal integration windows for speech, sinewave speech, and music - Lee, Hweeling; Noppeney, Uta (Frontiers in Psychology, 2014)
This psychophysics study used musicians as a model to investigate whether musical expertise shapes the temporal integration window for audiovisual speech, sinewave speech or music. Musicians and non-musicians judged the audiovisual synchrony of speech, sinewave analogues of speech, and music stimuli at 13 audiovisual stimulus onset asynchronies (±360, ±300 ±240, ±180, ±120, ±60, and 0 ms). Further, we manipulated the duration of the stimuli by presenting sentences/melodies or syllables/tones. Critically, musicians relative to non-musicians exhibited significantly narrower temporal integration windows for both music and sinewave speech. Further, the temporal integration window for music decreased with the amount of music practice, but not with age of acquisition. In other words, the more musicians practiced piano in the past three years, the more sensitive they became to the temporal misalignment of visual and auditory signals. Collectively, our findings demonstrate that music practicing fine-tunes the audiovisual temporal integration window to various extents depending on the stimulus class. While the effect of piano practicing was most pronounced for music, it also generalized to other stimulus classes such as sinewave speech and to a marginally significant degree to natural speech.